Non-renormalization conditions for four-gluon scattering in supersymmetric string and field theory - Berkovits, Nathan [UNESP]; Green, Michael B.; Russo, Jorge G.; Vanhove, Pierre (Springer, 2009)
The constraints imposed by maximal supersymmetry on multi-loop contributions to the scattering of four open superstrings in the U(N) theory are examined by use of the pure spinor formalism. The double-trace term k(2)t(8)(trF(2))(2) (where k represents an external momentum and F the Yang-Mills field strength) only receives contributions from L <= 2 (where L is the loop number) while the single-trace term k(2)t(8)(trF(4)) receives contributions from all L. These statements are verified up to L = 5, but arguments based on supersymmetry suggest they extend to all L. This explains why the single-trace contributions to low energy maximally supersymmetric Yang-Mills field theory are more divergent in the ultraviolet than the double-trace contributions. We also comment further on the constraints on closed string amplitudes and their implications for ultraviolet divergences in N = 8 supergravity.
Keywords: Extended Supersymmetry; Gauge Symmetry; Field Theories in Higher Dimensions